Perencanaan dan Pengelolaan Dana Infrastruktur Desa di Kampung Pasar Simpang Tiga Kecamatan Bukit Kabupaten Bener Meriah Tahun 2017 - Fauzan Fauzan; Dicky Armanda; Muhaddis Muhaddis; Nurmasyahyati Nurmasyahyati (Universitas 17 Agustus 1945, 2024)
This study aims to analyze the planning and management strategy of infrastructure fund allocation in Pasar Simpang Tiga Village, Bukit District, Bener Meriah Regency. This research was conducted in Pasar Simpang Tiga Village, Bener Meriah Regency. The research aims to understand the stages of planning and management of the infrastructure budget in Pasar Simpang Tiga Village, Bukit District, Bener Meriah Regency, as well as its impact on infrastructure development in the region. In this study, the researcher applies a qualitative approach with a descriptive analysis method. Data collection was carried out by conducting observations, interviews, and documentation studies. The results of the study show that in Pasar Simpang Tiga Village, Bukit District, Bener Meriah Regency, the planning and management process of village infrastructure funds uses the musrembang method. In this method, planning uses a top-down and bottom-up planning model that refers to the Bener Meriah Regency RPJM, the Bener Meriah Regency RPJMDesa, and the Bener Meriah Regency RTRW. The planning at Simpang Tiga Market was led by a team consisting of eleven members, including village reje, petue, kaur pembangunan , kaur evaluation, imem, and other figures. The results of the village meeting are then submitted to the sub-district to be evaluated and adjusted to the needs of the community. The impact of planning and management of village infrastructure funds in Pasar Simpang Tiga Village, Bukit District, Bener Meriah Regency has accelerated the development process in the village, both physically and non-physically. The positive impact of this is the increase in Village Original Income (PAD) of Pasar Simpang Tiga Village. However, the negative impact is the lack of optimal planning in prioritizing programs that are in accordance with the livelihood of the majority of the residents of Pasar Simpang Tiga Village, most of whom are palawija farmers such as potatoes, kul, carrots, red chilies, and green chilies, so this is not optimal in increasing the PAD of Pasar Simpang Tiga.